2020
DOI: 10.24265/horizmed.2020.v20n2.11
|View full text |Cite
|
Sign up to set email alerts
|

Un nuevo coronavirus, una nueva enfermedad: COVID-19

Abstract: La nueva pandemia de COVID-19 causada por el virus SARS-CoV-2 desafía actualmente a la humanidad. Este virus originario de murciélagos ha sido transmitido a humanos, probablemente, a través del pangolín en el mercado marino de Wuhan (China) a fines del 2019. Se disemina por gotitas de saliva o a través de materiales contaminados, por lo que es sumamente importante aislar a las personas infectadas que pueden ser sintomáticas o asintomáticas. El cuadro clínico típico se caracteriza por fiebre, tos seca, dificult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
0
6
0
12
Order By: Relevance
“…Los coronavirus son virus tipo ARN de sentido positivo que están envueltos y que van desde 60 nm a 140 nm de diámetro de aproximadamente 26-32 kilobases. Presentan espigas como proyecciones en su superficie que le dan una apariencia de corona bajo el microscopio electrónico; derivándose de este hecho el nombre coronavirus (Ashour et al, 2020;Quiroz-Carrillo et al, 2020;Salas-Asencios et al, 2020;Singhal, 2020). Se le han encontrado comúnmente en una amplia gama de hospederos, incluyendo aves, camellos, murciélagos, gatos civetas de la palmera, pangolines, ratones, perros y gatos (Tilocca et al, 2020).…”
Section: Generalidades De Coronavirus Y Zoonosisunclassified
See 1 more Smart Citation
“…Los coronavirus son virus tipo ARN de sentido positivo que están envueltos y que van desde 60 nm a 140 nm de diámetro de aproximadamente 26-32 kilobases. Presentan espigas como proyecciones en su superficie que le dan una apariencia de corona bajo el microscopio electrónico; derivándose de este hecho el nombre coronavirus (Ashour et al, 2020;Quiroz-Carrillo et al, 2020;Salas-Asencios et al, 2020;Singhal, 2020). Se le han encontrado comúnmente en una amplia gama de hospederos, incluyendo aves, camellos, murciélagos, gatos civetas de la palmera, pangolines, ratones, perros y gatos (Tilocca et al, 2020).…”
Section: Generalidades De Coronavirus Y Zoonosisunclassified
“…Desde finales de diciembre de 2019, nuestro planeta se enfrenta a un nuevo brote de una enfermedad viral infecciosa y zoonótica, conocida como COVID-19 (coronavirus disease-2019) (Ashour et al, 2020;Dzieciatkowski et al, 2020;Millán-Oñate et al, 2020;Quiroz-Carrillo et al, 2020;Reina, 2020;Salas-Asencios et al, 2020;Tilocca et al, 2020). Al evaluar los pacientes, muestra un cuadro clínico comparable al observado en el brote de SARS del 2003 y una historia compartida de visitas al mercado de mariscos de Huanan en Wuhan, provincia de Hubei, China (Cowling & Leung, 2020;Peeri et al, 2020;Salas-Asencios et al, 2020;Singhal, 2020;Zheng, 2020).…”
Section: Introductionunclassified
“…Due to the consequent number of patients requiring intensive care management in an emergency situation, the health personnel of these services must be prepared to provide specific organ support treatments and consider that certain treatments may be necessary for a large number of patients. Clinical presentation, comorbidities, age, number of days on mechanical ventilation, and risk of complications are factors that influence a potentially favourable outcome [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Considering what was stated by Barouki et al (2021) the current crisis caused by COVID-19 has been directly influencing commercial activities and their working conditions around the world, due to the lack of contact and physical displacement between their workers, customers and suppliers, which has been bringing a negative effect that will last through the years (Cestau, 2021). This lack of contact referred by Quiroz et al (2020) is caused by this highly contagious disease that spreads from person to person or through contaminated materials. That is why Qu et al (2021) states that many governments indicated that greater control of this disease will depend more on its prevention than on its treatment, consequently, they have been adopting mandatory social isolation measures and thereby trying to isolate the source of infection.…”
Section: Introductionmentioning
confidence: 99%